Role of Financial Literacy in Family Income Management in Luwu Regency - Dwi Cinta Lestari, Cinta Lestari; Antong, Antong; Goso, Goso (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to analyze the role of financial literacy in family income management in Bua District, Luwu Regency. Methodology: This research employs a quantitative approach using purposive sampling, involving 50 housewives as respondents. Primary data were collected through structured questionnaires measuring financial knowledge, financial attitude, and financial behavior, and analyzed using statistical regression techniques. Results: The results indicate that financial knowledge has a positive and significant effect on family income management. Financial attitude also shows a positive and significant influence, while financial behavior demonstrates a strong and significant positive effect on income management practices. Novelty: This study offers an integrated examination of three core dimensions of financial literacy—knowledge, attitude, and behavior—within the context of household financial management in a rural district. Findings: Financial behavior emerges as a crucial driver of effective family income management, supported by adequate financial knowledge and positive financial attitudes. Originality: The originality of this research lies in its focus on housewives in Bua District, providing localized empirical evidence on household financial literacy in Indonesia. Conclusions: Strengthening community-based financial education programs is essential to improve family income management and enhance household financial well-being. Type of Paper: Empirical Research Paper.